2021
DOI: 10.1108/apjml-03-2021-0221
|View full text |Cite
|
Sign up to set email alerts
|

The influence of e-customer satisfaction, e-trust and perceived value on consumer's repurchase intention in B2C e-commerce segment

Abstract: PurposeThis research study investigates the factors that influence e-customer satisfaction, e-trust, perceived value and consumers repurchase intention in the context of the B2C e-commerce segment. It investigates the mediation effect of e-customer satisfaction, e-trust and perceived value on repurchase intention. It also examines the moderating role of prior online experience.Design/methodology/approachBased on the adapted questionnaire, pre-recruited enumerators collected the data from five leading business … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1
43

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(128 citation statements)
references
References 60 publications
11
73
1
43
Order By: Relevance
“…A study conducted by Jhamb et al (2020) about the relationship between experience and attitude of consumers in the purchase of luxury brands products found that experience plays a significant role in building the attitude of consumers towards the products. Miao et al (2021) found that consumers' prior experience in performing a transaction in an e-commerce setting serve as a mediator that influence consumers' satisfaction and repurchase intention. Dai et al (2020) in their study related to consumers' intention to use autonomous vehicles, confirmed that a satisfying experience contributed to a higher degree of attitude.…”
Section: Consumer Experiencementioning
confidence: 98%
See 1 more Smart Citation
“…A study conducted by Jhamb et al (2020) about the relationship between experience and attitude of consumers in the purchase of luxury brands products found that experience plays a significant role in building the attitude of consumers towards the products. Miao et al (2021) found that consumers' prior experience in performing a transaction in an e-commerce setting serve as a mediator that influence consumers' satisfaction and repurchase intention. Dai et al (2020) in their study related to consumers' intention to use autonomous vehicles, confirmed that a satisfying experience contributed to a higher degree of attitude.…”
Section: Consumer Experiencementioning
confidence: 98%
“…The attitude of consumers is related to their satisfaction toward certain products or services. In the business-to-consumer ecommerce (B2C) segment, it is found that consumers' satisfaction influences the consumers repurchase intention (Miao et al, 2021).…”
Section: Consumer Satisfactionmentioning
confidence: 99%
“…Their reliance on political leaders is also crucial for their participation in political matters (Vigoda-Gadot, 2007). Researchers have reported a significant relationship between satisfaction and trust in organizational contexts (Miao et al, 2021;Wilson et al, 2021). For instance, Wilson et al (2021) asserted that when people are more satisfied with the administrative services, they trust organizations more.…”
Section: Citizens' Satisfaction and Citizens' Trustmentioning
confidence: 99%
“…Dalam berbelanja online, pelanggan dapat dengan mudah menemukan alternatif lain (Hsin Chang & Wang, 2011). E-satisfaction, e-trust, dan Perceived Value yang dirasakan oleh pelanggan memiliki peran penting dalam menciptakan repurchase intentions atau eloyalty (Miao et al, 2021). Perceived Value menurunkan keinginan pelanggan untuk beralih ke penyedia lain sehingga berpengaruh pada loyalitas (Anderson & Srinivasan, 2003).…”
Section: Perceived Valueunclassified